2020
DOI: 10.33715/inonusaglik.735467
|View full text |Cite
|
Sign up to set email alerts
|

Gebelerde Sağlik Algisi, Sağlik Okuryazarliği Ve İli̇şki̇li̇ Faktörler

Abstract: Bu çalışma gebelerde sağlık algısı, sağlık okuryazarlığı ve ilişkili faktörlerin değerlendirilmesi amacıyla yapılmıştır. Çalışmanın örneklemini Mart-Nisan 2017 tarihlerinde özel bir hastanenin NST polikliniğine başvuran ve araştırmaya katılmayı gönüllü olarak kabul eden 150 gebe oluşturmuştur. Veriler "Gebe Tanıtım Formu, Sağlık Algısı Ölçeği ve Sağlık Okuryazarlığı Ölçeği" ile yüz yüze görüşme yöntemi kullanılarak toplanmış olup Statistical Package for Social Sciences for Windows 20.0 istatistik paket program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…In a study conducted on the perception of health in pregnant women, it was demonstrated that the perception of health of pregnant women improved as their health literacy increased. 21 The high perception of health might also be due to the high education levels and high health literacy skills of pregnant women. Pregnant women obtained the highest score on the center of control subscale of the perception of health.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on the perception of health in pregnant women, it was demonstrated that the perception of health of pregnant women improved as their health literacy increased. 21 The high perception of health might also be due to the high education levels and high health literacy skills of pregnant women. Pregnant women obtained the highest score on the center of control subscale of the perception of health.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on the issue reported that 20% of the pregnant women had unplanned pregnancy. 20 Although the ratio of planned pregnancies was high, it seems that one every five women had an unplanned pregnancy. This finding suggests that pregnancies without preconception counseling could be associated with pregnant women's low health literacy levels.…”
Section: Discussionmentioning
confidence: 99%
“…There is a relationship between health literacy levels and health perception, and this affects decisions about receiving health services and choosing the right services. [20][21][22] Although pregnancy is a physiological process, pregnant women's quality of life is affected by factors such as limitations in physical activities, emotional changes, parity, gestational week, and having a planned pregnancy. [23][24][25] Studies in the literature show that health literacy level is also one of the factors affecting quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Akça ve arkadaşlarının (2020) gebelerle yaptığı çalışmada gebelik sayısı ile sağlık okuryazarlıkları arasında ilişki bulunmamıştır. 22 Bu çalışmada ortaya çıkan farklı sonucun primipar kadınların daha genç yaşta olmasından kaynaklandığı düşünülmektedir.…”
Section: Verilerin Değerlendirilmesiunclassified